Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1016/0969-2126(93)90016-a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the Awd nucleotide diphosphate kinase from Drosophila

Abstract: Regulatory properties of animal NDP kinases depend on interactions with other macromolecules, such as DNA and the product of the Drosophila prune gene. The Awd structure suggests an allosteric mechanism of action of NDP kinase where DNA is the effector and the protein undergoes a major conformational change, possibly dissociating to dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
79
2
5

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 28 publications
1
79
2
5
Order By: Relevance
“…In human cells, four members of the NDP kinase family encoded by the genes nm23-H 1 (8), nm23-H 2 (9), DR-nm23 (10), and nm23-H 4 (11) have been identified so far. A fifth isoform, nm23-H 5 was isolated very recently but it does not exhibit NDP kinase activity when overexpressed in bacteria (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In human cells, four members of the NDP kinase family encoded by the genes nm23-H 1 (8), nm23-H 2 (9), DR-nm23 (10), and nm23-H 4 (11) have been identified so far. A fifth isoform, nm23-H 5 was isolated very recently but it does not exhibit NDP kinase activity when overexpressed in bacteria (12).…”
mentioning
confidence: 99%
“…They catalyze the transfer of a phosphate from a nucleoside triphosphate to a nucleoside diphosphate via the formation of an enzymatic intermediate phosphorylated on a catalytic histidine residue (1). The crystal structures of NDP 1 kinases from several organisms including prokaryotes (2) and eukaryotes (3)(4)(5) have been determined. They all share a common subunit fold, built around a ␤␣␤␤␣␤ motif, also present in the "palm domain" of DNA polymerases (5).…”
mentioning
confidence: 99%
“…The currently known high-resolution crystal structures of NDPK are: tetrameric: Myxococcus xanthus [ 18]; hexameric: Dictyostelium discoideum [19], Drosophila melanogaster [20] and Homo sapiens nm23-H2, NDPK-HB [21]. However, Hamby et al [22] report NDPK-HB to be tetrameric in solution and preliminary gel filtration studies in our laboratory also suggested a smaller complex than a hexamer for NDPK-HB.…”
Section: Introductionmentioning
confidence: 78%
“…The crystal structure of Drosophila melanogaster awd and of Dictyostelium discoideum NDPK has been resolved (Chiadmi et al, 1993;Dumas et al, 1992). The enzyme is a symmetrical hexamer of identical subunits.…”
Section: Introductionmentioning
confidence: 99%